Revestimento, qualidade física e fisiológica de sementes de cenoura (Daucus carota L.) cv. Brasília - Soares, Flávio Humberto [UNESP] (2009)
The carrot is an important vegetable in Brazil, with production area of about 28,000 ha / year and the technique of coating of the seeds have been used for tillage. This research was performed at the Laboratory of Seed Analysis, Department of Plant Production, Faculdade de Ciências Agrárias e Veterinárias/UNESP, Câmpus de Jaboticabal, to evaluate four different concentrations of coating on three sizes of seed of the carrot and physical qualities physiological. We used three seed lots of carrot (Daucus carota L.) cv. Brasília, originated from different umbels of the same flower, and covered with inlay of 0%, 50%, 100%, 150% and 200% of the density of the seed. We evaluated the physical factors: water content, physical purity, weight of 1000 seeds, number of seeds per gram and Volumetric Weight, and physiological factors: the tetrazolium test, germination and emergence, and force the testing of first count of germination and Emergency and speed of germination index and Emergency. For the statistical analysis used the completely randomized design in factorial with four replications, and comparison of means was made using the Tukey test at 5% level of probability. According to the results concluded that the sizes of the seeds of carrot subjected to tests of physical evaluation respond differently to treatment of coating. It is recommended to use the technology of coating by the process of incrustation of up to 150% concentration, it does not interfere in any significant way to the main test of physiological seed quality of carrot cv. Brasília, regardless of size.